Firming up the capital base of the Austrian business sector - Consolidating Austria's business sector strengths and its social role in the face of new challenges - Dlugosch, Dennis (OECD Economics Department Working Papers, 2020)
While small- and medium sized firms in Austria are generally more productive, export more, and engage more in higher technology activities than in comparable countries, they need to adapt better to the knowledge economy to maintain their relative performance levels. The capital structure of Austrian SMEs are biased towards debt-financing and stronger equity, growth and venture capital markets would provide them with further resources for their long-term knowledge based investments. Skills shortages, in particular in advanced digital technologies, should be overcome. As around one third of all SMEs are up for ownership transmissions, ensuring successful business transfers will be crucial for maintaining the broad-based entrepreneurial dynamism. Meeting these challenges would also help to lift constraints on upscaling that many SMEs face and would provide the fruitful soil for future innovative activities. This Working Paper relates to the 2019 OECD Economic Survey of Austria (http://www.oecd.org/economy/austria-economic-snapshot/)